Saving Horatio Alger : Equality, Opportunity, and the American Dream - Reeves, Richard V. (Brookings essay., 2015)
Americans celebrate the Horatio Alger ideal, that all individuals can succeed by their own efforts in a level playing field, yet social mobility rates in America are now lower than those in Europe, risking America becoming an ossified, class-based society. Richard Reeves argues in this Brookings Essay that Alger is on the ropes, that the ideal of American egalitarianism is threatened by a variety of forces related to income, wealth, family structure and education. And yet the answers do not lie in the European model. Instead, Reeves argues, reviving the promise of the American Dream requires a quintessentially American solution, saving Horatio Alger.